Effect of mulch type and colour o9n growth and yield of tomato (Lycopersicon esculentum) - CHAKRABORTY, R C; SADHU, M K (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during winter seasons of 1991-92 and 1992-93 to study the effect of different mulch types and colours on growth and yield of tomato (Lycopersicon esculentum Miller nom. cons.). weed growth, soil temperature. moisture and salinity. Polyethylene mulches. irrespective of colour, were superior to rice (Oryza satation(L.) straw or water-hyacinth [Eichhornia crassipes (e. Martius) SolmsLaub.] mulch in improving the growth and yield of tomato, but they suppressed the weed growth significantly. Among the mulch colours, black and red polyethylene increased the plant height by 23.8 and 30.9% respectively and the leaf number by 42% compared with the control, Black colour advanced the flowering period by 10 days and red colour by 11 days. Early flowering, greater number of fruits/plant and larger fruit size with red and black polyethylene resulted in 77.0 and 73.3% higher yield respectively compared with the control Black polyethylene completely suppressed the weed growth; other colours also checked the weed growth (blue colour by 96.2% and white by 77.4%), whereas clear polyethylene and natural mulching materials (such as rice straw and water· hyacinth) were markedly less efficient. Higher soil temperature (2-3oC above the control), greater soil·moisture conservation (31.5-67.7%) and lower salinity level (36.7 59.8%) were also observed with polyethylene mulches; but mulch colour had no appreciable effect, Black polyethylene was found most economical.